Integration of Local Wisdom in the Formulation of Kombucha Shampoo from Job's Tears (Coix lacryma-jobi L.) Leaves as an Anti-Dandruff Agent against Pathogenic Fungi of the Scalp - Tri Saptari Haryani; Yugga Tri Surahman; Firman Rezaldi; Erni Suminar; Syariful Mubarok (Jurnal Penelitian Pendidikan IPA, 2026)
Dandruff is a common scalp disorder primarily associated with the activity of lipophilic fungi of the genus Malassezia, which can cause irritation, itching, and decreased quality of life. The widespread use of chemical-based anti-dandruff agents such as ketoconazole and zinc pyrithione may lead to side effects, including skin irritation, microbial resistance, and disruption of the scalp microbiota. Therefore, the development of safer and more sustainable natural alternatives is urgently needed. This study aims to explore the formulation of a natural anti-dandruff shampoo based on kombucha-fermented hanjeli leaves (Coix lacryma-jobi L.) by integrating local wisdom and modern biotechnology approaches. Kombucha fermentation produces various bioactive compounds, including organic acids, enzymes, and phenolic substances, which exhibit antifungal activity against Malassezia spp. Meanwhile, hanjeli leaves contain flavonoids, phenolics, and polysaccharides with antioxidant and antimicrobial potential. The combination of these two components is expected to enhance antifungal efficacy while maintaining scalp health. This study highlights the potential of kombucha-based hanjeli leaf shampoo as a natural, effective, and sustainable anti-dandruff product, contributing to the development of locally sourced pharmaceutical and cosmetic innovations